Adapting stigma mechanism frameworks to explore complex pathways between intersectional stigma and HIV-related health outcomes among women living with HIV in Canada. (July 2019) - Logie, Carmen H.; Williams, Charmaine C.; Wang, Ying; Marcus, Natania; Kazemi, Mina; Cioppa, Lynne; Kaida, Angela; Webster, Kath; Beaver, Kerrigan; de Pokomandy, Alexandra; Loutfy, Mona
Highlights: Intersectional stigma research examining pathways to HIV outcomes is limited. Adapted conceptual frameworks to examine intersectional stigma and health outcomes. Stigma interacted with social/institutional support to increase depression. Depression led to maladaptive coping, lowering adherence and CD4 count. Argues for multi-level strategies, including women-centred HIV care.